Mortality after traumatic brain injury and the effect of posttraumatic epilepsy. (28th August 2018) - Uski, Jessina; Lamusuo, Salla; Teperi, Simo; Löyttyniemi, Eliisa; Tenovuo, Olli
Abstract : Objective: To assess the effect of posttraumatic epilepsy (PTE) on mortality and causes of death after traumatic brain injury (TBI). Methods: Medical reports were collected retrospectively of patients who sustained TBI between 1996 and 2013. After defining patients with PTE and picking up 2 non-PTE matched TBI controls for every patient with PTE, the database included 714 patients. Demographic data, cause and mechanism of injury, nature of injury (focal injury, intracranial bleeding), time from accident to first seizure, remission rates, neurosurgical operations undertaken, and mortality data were collected. Results: Of the 714 patients, 555 (77.7%) were men and 159 (22.3%) were women. There was an obvious increase in long-term mortality in patients with PTE compared to control TBI patients. This increase became evident after about 1 year from the injury, when approximately 95% of both non-PTE and PTE patients were alive; after that, the difference in mortality increased. The difference remained significant at least up to 15 years from the injury, when around 65% of non-PTE patients with TBI were alive compared to only 45% of patients with PTE. In patients with PTE, the mortality was 1.75 times higher ( p = 0.0001). There was no significant difference in causes of death. Conclusion: This study shows that long-term mortality is higher in patients with PTE than other patients with TBI, although the reasons for this difference remain unclear.